Stubble management of Medicago polymorpha L. and pod consumption by grazing ewes during summer - Fois N.; Ligios S.; Sitzia M. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
A research on pod, seed production and consumption of Medicago polymorpha L. grazed by sheep was carried out during summer 1998. Pod, seed production, stubble availability, chemical composition and their consumption by sheep were measured. Pod availability resulted 3.1 t ha-1 whereas seed production was 1.4 t ha-1. The crude protein content was 21 per cent and 11 per cent in pods and stubble, respectively. During the trial the ewe intake of mature pods on average was 1200 g DM head day-1 corresponding to 540 g head day-1 of seed. No effects were found on live weight and body condition score change. The high seed yield of burr medic assures a large seed bank and, in the meantime, its high quality represents an important feed resource for sheep grazing stubble during summer.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)